Impacts of Continuous Cropping on Fungal Communities in the Rhizosphere Soil of Tibetan Barley - Yao, Youhua; Zhao, Yuan; Yao, Xiaohua; Bai, Yixiong; An, Likun; Li, Xin; Wu, Kunlun (Frontiers in Microbiology, 2022)
Microbial community structures and keystone species play critical roles in soil ecological processes; however, their responses to the continuous cropping of plants are virtually unknown. Here, we investigated the community dynamics and keystone species of fungal communities in the rhizosphere soils of continuously cropped Tibetan barley (a principal cereal cultivated on the Qinghai–Tibetan Plateau). We found that the Chao1 and Phylogenetic Diversity (PD) indices decreased with increased cropping years. The relative abundance of the genera Cystofilobasidium, Mucor, and Ustilago increased with the extension of continuous cropping years, whereas Fusarium showed the opposite pattern. Furthermore, long-term monocropped Tibetan barley simplified the complexity of the co-occurrence networks. Keystone operational taxonomic units (OTUs) changed with continuous cropping, and most of the keystone OTUs belonged to the phylum Ascomycota, suggesting their important roles in rhizosphere soil. Overall, this study revealed that the continuous cropping of Tibetan barley impacted both on the richness, phylogenetic diversity, and co-occurrence network of fungal community in the rhizosphere. These findings enhance our understanding of how rhizosphere fungal communities respond to monocropped Tibetan barley.